Vitamin D Supplementation reduces Atorvastatin induced Myopathy in Dyslipedemic patients - Nadeem, Maryam; Shahzad Alam, Saadia; Noor Zahra, Syeda Mah E; Daniyal, Shoaib M; Zia, Huma; Saqib, Maryam; Nadeem, Maryam (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Dyslipidemia is becoming one of the most common problems worldwide predisposing towards atherosclerotic cardiovascular events and other issues like obesity. Statins are imperative for treating dyslipidemia. However statin-intolerance is a major hurdle due to the myopathy incurred with their usage, ranging from mild aches and pains without CPK elevation to marked increase in CPK levels with myonecrosis and even death in rare cases. Aim: Local identification of dyslipedemic patients with reduced vitamin D levels and intolerance to ≥2 statins (especially Atorvastatin), exhibiting statin induced myopathy with CPK elevation. Assessment of 3 months vitamin D therapy on myopathy and patient compliance to statins Place and duration of study: A 13 months study conducted in Army Cardiac Center Lahore . Methods: Upon Ethical Board Clearance (Ref No:F.39/NHRC/Admn/IRB/40)(IRB- Number: 1547) 60 dyslipidemic patients ranging from 40-70years of age, having CPK confirmed myopathy (CK levels >120micrograms/L) and intolerance to ≥2 statins (including Atorvastatin) along with hypovitaminosis D were assessed for enrollment based on strict inclusion and exclusion criteria at Army Cardiac Center Lahore. Results: Baseline investigations including CBC, renal, liver and thyroid function tests, vit D, vit B12, hepatitis B, C, FBS, CK, CK MB and lipid profile were performed.At the end of the study at 3rd month (2ndfollowup) investigations such as 25 hydroxy vitamin D levels, presence or absence of muscular pain as symptom of myopathy and CPK with its isoenzymes CK MB levels were repeated and compared with the baseline values Conclusion: In this study it is concluded that by replenishing vitamin D levels, Atorvastatin induced myopathy improves leading to more compliance towards the drug and resulting in improvement in lipid profile.